The Right to Social Security of the Elderly People in Bangladesh: A Focus on Human Rights Violation - A K M Mahmudul Haque; Md. Zahid Hossain; S M Akram Ullah (Journal of Social Science)
As the part of vulnerable groups, elderly people hold the rights to social security according to the constitution of the People’s Republic of Bangladesh and the Universal Declaration of Human Rights (UDHR). This study has been launched for the purpose of revealing the picture of the facts and figures of the deprivation of social security as human rights violation of the elderly people in Bangladesh. The study has been done based on both primary and secondary sources of data. It reviewed the social security programs regarding elderly people such as, old age allowance, widow allowance and disability allowance. The study found that the government has taken several programs. But these programs have not been successful to achieve cent percent success due to corruption, nepotism and inadequate national economy. Most of the elderly people of Bangladesh cannot enjoy properly the rights to social security. For raising awareness about rights and responsibilities, enhancing proper ethical education can be helpful to remove these obstacles. Raising massive social movement against corruption and nepotism can also be helpful as the beacon of hope in the way of ensuring social security of the elderly people in Bangladesh.